Domain inhibition linked low activity of Phe-tRNA synthetase for para-fluorophenylalanine in a mutant of Aspergillus nidulans - N. K.T. SINGH; B. N. TIWARY; U. SINHA (Fungal Genetics Reports, 1990)
A number of different mechanisms for p-fluorophenylalanine (FPA) resistance have been described in Aspergillus nidulans. We present data on a new locus for FPA resistance and its biochemical change. Before this report, 20 FPA resistant loci conferring resistance to this amino acid analogue have been identified by us (Tiwary et al. 1987 Curr. Microbiol. 15:305-311) and two by Kinghorn and Pateman (1975 J. Gen. Microbiol. 86:174-184). These mutations have been mapped on five out of eight linkage groups of A. nidulans, there being no report of any mapping of FPA resistant loci on linkage groups III,IV or VII. A new class of FPA resistant mutants exhibiting a reduced level of phenylalanyl-tRNA synthetase was identified in a selection scheme using nitrate as the nitrogen source (Tiwary et al. 1987 Mol. Gen. Genet. 209:164-169). We have slightly modified the technique for the selection of analogue resistant mutants by substituting aspartic acid (25 mM) for sodium nitrate (0.6%) as the nitrogen source in the Czapek-Dox medium in the presence of 30 mg/ml FPA. A higher rate of survival was found on medium containing aspartate than nitrate.